When Helping Hurts: How to Alleviate Poverty Without Hurting the Poor and Yourself & God Knows There’s Need: Christian Responses to Poverty - Davidson, Theresa C. (Christian scholar's review, 2010)
When Helping Hurts: How to Alleviate Poverty Without Hurting the Poor and Yourself Steve Corbett and Brian Fikkert Published by Moody Publishers in 2009 pp / $ / Amazon Goodreads God Knows There’s Need: Christian Responses to Poverty Susan R. Holman Published by Oxford University Press in 2009 pp / $ / Amazon Goodreads These...